The Lanz (R) endotracheal tube decreases tracheal injury in dogs - Abud, TMV; Braz, JRC; Martins, RHG; Gregorio, E. A.; Saldanha, J. C.; Raiza, ACP (Canadian Anesthesiologists Soc, 2005)
Purpose: To determine, in dogs anesthetized with nitrous oxide (N2O), whether the endotracheal tube (ETT) cuffed with a Lanz (R) pressure regulating valve decreases the tracheal consequences of tracheal intubation.Methods: Sixteen mixed-breed dogs were allocated to two groups according to the ETT used: Control group (n = 8) Rusch ETT, and Lanz group (n = 8) - ETT with Lanz (R) pressure regulating valve. The ETT cuffs in both groups were inflated with air to an intracuff pressure of 30 cm H2O. Anesthesia was induced and maintained with pentobarbitone and N2O (1.5 L(.)min(-1)) and O-2 (1 L(.)min(-1)). ETT cuff pressures were measured before (control) and 60, 120, and 180 min during N2O administration. The dogs were sacrificed, and biopsy specimens from four predetermined areas of the tracheal mucosa in contact with the ETT were collected for light and scanning electron microscopy (SM) examination.Results: Cuff pressures in the Control group were higher than in the Lanz group at all time points studied (P < 0.001), with an increase over time only in the Control group (P < 0.001). Median neutrophilic inflammatory infiltration values of the epithelial surface, and in the subepithelial layer in contact with the cuff, were higher in the Control group as compared to the Lanz group (3.0 vs 1.0 and 3.0 vs 1.5 respectively) (P < 0.05). on SM examination, median histological grades were higher in the Control group compared to Lanz group (2.9 vs 1.9 respectively), (P < 0.05).Conclusions: the Lanz (R) ETT decreases tracheal mucosal injury in dogs.